Guide :

If 4.5 is equal to 423. What is 4.1 equal to ?

I was given an answer of 363. But I do not know why ? Can someone explain. Thank you.

Research, Knowledge and Information :

What does 3/4 + 5/8 equal? - Quora

What does 3/4 + 5/8 equal? Update Cancel. Answer Wiki. ... In this case, they are fourths (4 equal parts that make 1 whole) ... If 4 equals 5, ...

1/4 is equal to a 4 b 0.5 c 1 d 0.25 A fraction can be ...

Unformatted text preview: 1/4 is equal to: a) 4 b) 0.5 c) 1 d) 0.25 A fraction can be expressed as a decimal by dividing the denominator into the numerator.

If 1=5 , 2=15 , 3=20 , 4=25 then what is 5 equal to? - Quora

“If 1=5 , 2=15 , 3=20 , 4=25 then what is 5 equal to?” The answer is “potato”. An implication “if p, then q” has the property that if p is false, the ...

What does 4/5 x 1 1/6 equal - Fandom powered by Wikia

What does 4/5 x 1 1/6 equal? Edit. Edit source History Talk (0) Share. This question is awaiting an answer... Please leave this field blank unless you are answering ...

Fractions - Grade 5 Math Questions With Solutions and ...

... n must be equal to 3 and 5/6. Check 11 + 1 ... are all smaller than 1. 7/6 is the largest fraction. The remaining 3 fractions 3/5 , 1/3 , 4/9 can be compared ...

Equal to | Define Equal to at Dictionary.com

Equal to definition, as great as; the same as (often followed by to or with): ... If A equals B and B equals C, then A equals C. 12. to make or do something equal to:

1.5 is equal to what fraction - Free Math Help Online

1.5 is equal to what fraction. ... The fraction form of 1.5 is `= 15/ 10.` It can be simplified further as follows. By dividing the numerator and denominator by 5

Puzzles/Arithmetical puzzles/Four 4s Equal.../Solution ...

Solution to Puzzles/Arithmetical puzzles/Four 4s Equal... Contents. 1 1; 2 2; 3 3; 4 4; 5 5; 6 6; 7 7; 8 8; 9 9; 10 10; 11 11; 12 12; 13 13; 14 14; 15 15; 16 16; 17 ...

y=sqrt(x)-4x, 0<=x <=4 max: at x=0, y=0 . . min: at x=4, y=2-8=-6

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2 Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4 Subproblem 3 Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1 Solution x = {0, -4, 1}

show that the function f(x)= sqrt (x^2 +1) satisfies the 2 hypotheses of the Mean Value Theorem

f(x) = sqrt(x^2 + 1) ; [(0, sqrt(8)] Okay, so for the Mean Value Theorem, two things have to be true: f(x) has to be continuous on the interval [0, sqrt(8)] and f(x) has to be differentiable on the interval (0, sqrt(8)). First find where sqrt(x^2 + 1) is continous on. We know that for square roots, the number has to be greater than or equal to zero (definitely no negative numbers). So set the inside greater than or equal to zero and solve for x. You'll get an imaginary number because when you move 1 to the other side, it'll be negative. So, this means that the number inside the square root will always be positive, which makes sense because the x is squared and you're adding 1 to it, not subtracting. There would be no way to get a negative number under the square root in this situation. Therefore, since f(x) is continuos everywhere, (-infinity, infinity), then f(x) is continuous on [0, sqrt(8)]. Now you have to check if it is differentiable on that interval. To check this, you basically do the same but with the derivative of the function. f'(x) = (1/2)(x^2+1)^(-1/2)x2x which equals to f'(x) = x/sqrt(x^2+1). So for the derivative of f, you have a square root on the bottom, but notice that the denominator is exactly the same as the original function. Since we can't have the denominator equal to zero, we set the denominator equal to zero and solve to find the value of x that will make it equal to zero. However, just like in the first one, it will never reach zero because of the x^2 and +1. Now you know that f'(x) is continous everywhere so f(x) is differentiable everywhere. Therefore, since f(x) is differentiable everywhere (-infinity, infinity), then it is differentiable on (0, sqrt(8)). So the function satisfies the two hypotheses of the Mean Value Theorem. You definitely wouldn't have to write this long for a test or homework; its probably one or two lines of explanation at most. But I hope this is understandable enough to apply to other similar questions!

Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Factor a trinomial. (-9 + -1x)(2 + -3x) = 0 Subproblem 1 Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9 Subproblem 2 Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667 Solution x = {-9, 0.6666666667}

find the intercepts with the axes or asymptotes : y=2sin(3x+30deg) with domain -pie/3 <or equals to x < or equals to pie/2

y-intersept be weer x=0, so plug in intu y=2*sine(3x+30 deg) y=2*sine(30) at x=0 sine(30 deg)=0.5, so y=2*0.5=1 x-intersept...set y=0, so 2*sine(3x+30)=0 so sine(3x+30)=0 sine=0 at (....)=0, so 3x+30=0 so 3x=-30 x=-10 deg

integral from 0 to pi where f(x)= 5sinx if 0<or equal to x<pi/2, 3cosx if pi/2<or equal to x<pi

answer this problem:Find the DEFINISI INTEGRAL FOURIER  representation of the function ,f(x)={0 ,x<0 } f(x)=pi/2 x=0,f(x)=pi*exp^x x>0

3x squared minus 7x equals 0

3x squared minus 7x equals 0 in my math homework...solve the quadratic equations by factoring 3x^2 - 7x = 0 When we factor this, we will have: (3x + a)(x + b) = 0 We need an a and b such that 3b + a = -7, and ab = 0. We know ab has to equal zero, because there is no constant term following the 7x. If we set a = 0 and b = -7/3, we will have what we are looking for. (3x + 0)(x - 7/3) = 0 Multiply that out, and we get: 3x^2 + 0x - 3(7/3)x - 0 = 0 3x^2 + 0x - 7x - 0 = 0 3x^2 - 7x = 0,  which is what we started with.

Find the solution set for each rational inequation. Graph the solution set on a number line.

(x+3)(x-2)/((x+2)(x-1))≥0. We need to look at various intervals marked by -3, -2, 1, 2 on the number line. x≤-3 satisfies the inequality; -3-3. (x-2)/(x^2-3x-10)<0. This is (x-2)/((x-5)(x+2))<0. Disallowed values are 5 and -2. Significant values are -2, 2, 5; x<-2 satisfies; -25 fails.

n^3-9n^2+20n prove that it is divisible by 6 for all integers n greater or equal to 1

Factor the given expression.   We have: n³-9n²+20n=n(n-4)(n-5) ··· Ex.1 If Ex.1 is divisible by 6, Ex.1 is also divisible by two prime factors of 6, 2 and 3. (6=2x3) A. If n is odd, (n-5) is even.   If n is even, (n-4) is also even.   Therefore, n(n-4)(n-5) is always a multiple of 2. B. If Exp.1 is divisible by 3, the remainder is 0,1,or 2. If n ≡ 0 (mod 3), n-4 ≡ -4 ≡ -1 (mod 3), and n-5 ≡ -5 ≡ -2 (mod 3), that is: n is a multiple of 3. If n ≡ 1 (mod 3), n-4 ≡ -3 ≡ 0 (mod 3), and n-5 ≡ -4 ≡ -1 (mod 3), that is: (n-4) is a multiple of 3. If n ≡ 2 (mod 3), n-4 ≡ -2 (mod 3), and n-5 ≡ -3 ≡ 0 (mod 3), that is: (n-5) is a multiple of 3. Therefore, n(n-4)(n-5) is always a multiple of 3. CK: If n=1, n(n-4)(n-5)=1(-3)(-4)=12, 12(n=2), 6(n=3), 0(n=4), 0(n=5), 12, 42, 96, 180 … CKD.  Therefore, n³-9n²+20n is divisible by 6 for all integers greater than or equal to 1.

(13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: x + -3x = -2x -3 + -2x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Reorder the terms: -3 + -2x + x2 = 5 + -5 + 3x + -3x + -1x2 + x2 Combine like terms: 5 + -5 = 0 -3 + -2x + x2 = 0 + 3x + -3x + -1x2 + x2 -3 + -2x + x2 = 3x + -3x + -1x2 + x2 Combine like terms: 3x + -3x = 0 -3 + -2x + x2 = 0 + -1x2 + x2 -3 + -2x + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 -3 + -2x + x2 = 0 Factor a trinomial. (-1 + -1x)(3 + -1x) = 0 Subproblem 1 Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1 Subproblem 2 Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3 Solution x = {-1, 3}